Analisis Efektivitas Kumulasi Perkara Permohonan Itsbat Nikah dan Gugat Cerai - Nurul Fadilah (TAFAHUS: JURNAL PENGKAJIAN ISLAM, 2022)
Legal certainty for husbands, wives, and children in the household is very much needed; therefore, registration of marriages is very important. However, there are still marriages among the people who do not have valid official documents, so they lack legal certainty. This study intends to examine how the Gunung Sugih Religious Court decides on a marriage application and a divorce suit filed simultaneously by itsbat. This type of research is a case study using qualitative analysis methods to examine the factors of legal justification and factors considered by the judge's judgment, using the information obtained by the researcher from the decision of the Gunung Sugih Religious Court with Case Number: 0333/Pdt.G/2018/PA. Gsg. Research data were collected through interviews with judges and religious court employees, as well as through documentation. Inductive conclusions are drawn after the analysis of the collected data. The results of the research show that decision number 0333/Pdt.G/2018/PA.Gsg. Based on the information gathered by the panel of judges and the fact that the plaintiff and the defendant in this case were legally married according to state and religious law, the judge decided to grant the request for ishbat nikah and the divorce claim. However, in order to be able to file for divorce, it is necessary to have a Marriage Legalization Determination from the Religious Court because the marriage certificate is lost. The judge's considerations are influenced by the conditions that have been met, as well as the evidence that has been prepared by an authorized official and affixed with sufficient stamp duty to be declared accepted and considered valid evidence under the law.